Cellulosic liquid crystals for films and fibers. Issue 2 (3rd July 2017) - Canejo, J. P.; Monge, N.; Echeverria, C.; Fernandes, S. N.; Godinho, M. H.
ABSTRACT: Cellulose, the most abundant natural polymer on earth, is used in numerous applications in our day-to-day life. However, the discovery that cellulose-based systems could lead to the formation of liquid crystalline phases only dates to the 1970s. Compared with all known applications of cellulose, the liquid crystalline behavior has been less considered. Associated with this are the low solubility of cellulose and the existence of a chiral nematic precursor solution and its processing under the action of a shear field, which is used to produce fibers and films. In this review, we first conduct a short review of the main features of cellulosic liquid crystalline phases including the main textures observed by polarizing optical microscopy and the cholesteric phase characteristics of thermotropic and lyotropic systems observed for cellulose and cellulose derivatives. Then, we focus on the rheological properties of liquid crystalline solutions and special attention is given to the formation of striations developed during shear and the formation of the band texture, which appears during the relaxation process. Among the different techniques used, special emphasis is given to the results obtained by coupling rheology with optical microscopy (Rheo-optics) and nuclear magnetic resonance (Rheo-NMR) techniques. Some examples described in the literature, related to the use of cellulose and cellulose derivatives liquid crystals to the production of structural color scaffolds, stimuli-responsive films and fibers, are addressed. In these systems, the initial cholesteric phase determines the unique properties exhibited by the films and the fibers produced from cellulosic liquid crystalline systems.